Analysis of the Impact of Changes in the Functional Distribution of Income on Aggregate Demand - Statkus, Justinas; Tamašauskienė, Zita (Socialiniai tyrimai, 2020)
Over the past decades, there have been significant changes in the functional income distribution. The decreasing wage share in national income, the causes and consequences of this phenomenon have become the subject of both research and political debate. Over the past decade, research in the most developed countries has shown that economic growth has been influenced by wage share rather than a profit share. The decline in the wage share in countries’ incomes may have been the cause of slowing economic growth or a sluggish post- crisis recovery (Blecker, 2016). The decline in the wage share is one of the key aspects of changes in income change, which also includes an increase in personal income inequality (Hein, 2015). Although much research has been done on changes in the distribution of personal income, the problem of the functional income distribution has not been sufficiently explored.The concepts of income distribution and functional income distribution seem similar at first glance, but this is not the case. The distribution of income is described as the income earned in a country’s economy distributed among the total population. This indicator is usually calculated at the household level (i.e. the total income of all household members is calculated), taking into account the number of household members and their age. Meanwhile, the functional distribution of income is described as the distribution of national income between the two factors of production – labour and capital. This means that income is distributed between employees and capital owners. Theoretically, it is stated that 2/3 of  income goes to labour and 1/3 to capital. The impact of changes in wage and profit shares on aggregate demand is quite complex and depends, among other things, on the country specification, data sources and coverage, the measurement of different variables and the statistical methods used in the surveys. Bhaduri and Marglin (1990) analyzed the impact of changes in the functional distribution of income on consumption,  investment,  exports,  and  imports. The essence of the model is that wage share has a dual effect on the economy, at the same time it is business expenditures and the main factor of private household consumption (Storm andNaastepad, 2017). As the effects of changes in the functional distribution of income impact the components of aggregate demand in national income differently, the ultimate impact on aggregate demand is not clear. If the decline in the wage share has a positive effect on aggregate demand, it is considered to be profit- led aggregate demand, if it has a negative effect, demand is wage-led.In the macroeconomic  field,  aggregate  demand is understood as the total amount of final products and services produced in a country over a period of time that buyers can and want to purchase at a certain price level. Gross demand consists of 4 components: consumption, investment, exports and imports. This is the demand for the country’s gross domestic product (Basu and Gautham, 2019). By way of analysis, the main determinants of aggregate demand included in the researches can be identified. The most frequently included  factors  in the investment function are income, wage, profit, less frequently used factors are inequality of personal income and marginal propensity of employees to consume. In investment functions, the main factors are income, profit and wage income. Factors such as capacity utilization and business expectations are less frequently included in investment functions. The rest of the world’s income and export prices are usually included factors in the export function. However, less frequently included factors in the export function are housing assets. On the other hand, import prices and unit labor costs are the most commonly influenced factors in the import function. Less commonly used factors in the import function are investment costs.Based on the Bhaduri and Marglin model, a number of studies have been conducted to assess the impact on consumption, investment, import, export and to determine whether the economy is wage-led or profit-led (Naastepad and Storm, 2006; Hein and Vogel, 2008; Stockhammer and Ederer, 2007; Stockhammer and Stehrer, 2011; Onaran and Galanis, 2014). In their research, the authors make a clear distinction in which countries aggregate demand is profit-led and which is wage-led. In empirical studies, economic growth is stimulated either by exports or domestic demand. In the post-war period, most studies found wage-led domestic demand in almost all countries, but net exports can turn a particular economy into a profit-led one. Some researchers have studied the impact of changes in the functional income distribution on aggregate demand in individual countries, while others in groups of countries. In most of the countries (UK, Italy, Netherlands, Austria, Norway, Sweden, Denmark) analyzed in the empirical studies, domestic and aggregate demand was wage-led. Also, economic growth in most countries was driven more  by  domestic  demand  than by export. One of the worst examples of increasing economic growth is noticeable in Spain. The aim was to do this through internal devaluation – by reducing unit labor costs. However, the increase in net exports was smaller than the decrease in domestic demand, which had a negative impact on economic growth.
Keywords: functional income distribution; consumption; investment; exports; imports; aggregate demand